SEKTOR BASIS EKONOMI PERTANIAN DI PROVINSI RIAU (PERIODE 1997-2015) - Alhaq, Qowiy; Basri, Syafril; Setiawan, Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to determine the basic sector and non-sector economic base of agriculture in the province of Riau. The object of this research is Riau Province which that region dominated by agriculuture sector. The analytical method used in this research is descriptive and quantitative methods. This research uses an annual datas from 1997 to 2015 which get from Riau Province Statistical and analyzed with Location Quotient (LQ), Share Analysis and Typology Klassen. Research of Location Quotient and Typology Klassen concluded that the plantation subsector, forestry subsector, also subsector of agriculture and hunting are the economic base in the agricultural sector in the province of Riau. This is indicated by the value of PB ≥ 0 and LQ ≥ 1. Instead subsector foodstuffs, farms subsector and fisheries subsectors become non bases sector because value PB ≥ 0 and LQ <1. Shift Share analysis test results shows that on 1997 to 2010, subsector foodstuffs and fisheries subsector has a proportional share of positive value. While the plantation subsector, farms and forestry sub-sector is negative. The result on 2011-2015 shows that the proportional share of the food sub-sector, subsector horticulture and forestry subsector is negative and it’s positive for fisheries subsector, plantation, farms and agriculture.Keywords : location quotient, Klassen typology, Shift share, GDP, Economic base